2016
DOI: 10.1021/acs.jmedchem.6b01333
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship for Sulfonamide Inhibition of Helicobacter pylori α-Carbonic Anhydrase

Abstract: α-Carbonic anhydrase of Helicobacter pylori (HpαCA) plays an important role in the acclimation of this oncobacterium to the acidic pH of the stomach. Sulfonamide inhibitors of HpαCA possess anti-H. pylori activity. The crystal structures of complexes of HpαCA with a family of acetazolamide-related sulfonamides have been determined. Analysis of the structures revealed that the mode of sulfonamide binding correlates well with their inhibitory activities. In addition, comparisons with the corresponding inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…Developed as an inhibitor of hCAs, EZA is also known to inhibit activity of H. pylori α-and β-carbonic anhydrases (HpαCA and HpβCA) [12,13]. The crystal structures of HpαCA bound to EZA and related sulfonamides demonstrated that these compounds act as competitive inhibitors mimicking the transition state of the reaction, and that their structure correlates well with their in vitro inhibitory properties [14,15]. These observations suggest that the EZA inhibition of activity of H. pylori carbonic anhydrases likely plays an important role in the mechanism of its antibacterial action, although no spontaneous HpαCA and HpβCA mutants with resistance to EZA have been isolated so far.…”
Section: Open Accessmentioning
confidence: 99%
“…Developed as an inhibitor of hCAs, EZA is also known to inhibit activity of H. pylori α-and β-carbonic anhydrases (HpαCA and HpβCA) [12,13]. The crystal structures of HpαCA bound to EZA and related sulfonamides demonstrated that these compounds act as competitive inhibitors mimicking the transition state of the reaction, and that their structure correlates well with their in vitro inhibitory properties [14,15]. These observations suggest that the EZA inhibition of activity of H. pylori carbonic anhydrases likely plays an important role in the mechanism of its antibacterial action, although no spontaneous HpαCA and HpβCA mutants with resistance to EZA have been isolated so far.…”
Section: Open Accessmentioning
confidence: 99%
“…As carbonic anhydrases were considered the likely targets for the anti-H. pylori activity of sulfonamides [12][13][14][15] , the genes for aand b-carbonic anhydrases were sequenced in the parental strain and in MutE. No mutations were found, eliminating the possibility that amino acid changes in these enzymes caused the resistance phenotype.…”
Section: Identification Of Genetic Determinants Linked To Eza Resistancementioning
confidence: 99%
“…Analysis of the crystal structures of HpaCA in complex with either AAZ or MZA 14 revealed that these sulphonamides act as activesite inhibitors that mimic the transition state of the reaction catalysed by the enzyme. Furthermore, the crystal structures of HpaCA in complex with a series of AAZ-related sulphonamides, including EZA, revealed that the mode of sulphonamide binding to HpaCA correlates well with their inhibitory activities 15 . Cumulatively, these data have raised a question of whether the HpaCA inhibition by sulphonamides would result in killing H. pylori.…”
Section: Introductionmentioning
confidence: 98%
“…Both metalloenzymes have been described to be essential for acid acclimation, biosynthetic reactions, bacterial survival, and colonization of the stomach and duodenum [67,68,[70][71][72]. They are targeted by sulphonamide antimicrobial agents and phenol-derivatives [68,69,71].…”
Section: Ph Homeostasismentioning
confidence: 99%